If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying rs = t Solving rs = t Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Divide each side by 's'. r = s-1t Simplifying r = s-1t
| (1)/(2)6= | | -x^2+19x+42= | | 2y+4y=90 | | y+2x-3=0 | | (-xy^2)(2xy)(-3y)= | | 8x-4=-10x+5 | | 16x^3-9x^2=0 | | -4(x+1)-10=19+3 | | 20x^3+28x^2+60x=0 | | -5+2(x-2)= | | 6x+10+7x=75 | | 7(2x+1)-4x= | | -18+8x=-7(x-4)-8x | | 2x-6y=14 | | 8x-x(x+4)= | | -3(3x-6)-2x= | | 3x+5+6x-14=180 | | 3y^4-4y^3-4y^2=0 | | -4(x+3)+5= | | x+2(x-4)=1+3(x+2) | | 7y-1=11y+19 | | 2+6lnx=11 | | x+2(x-4)=1+3(x-2) | | -4(-5)(-5)= | | -30+8x=-5(6-8x) | | 20(9-.8y)+16y=180 | | 4=6/2(x)-3 | | vm=w | | 9x+37=6x+8 | | 6(5x+12)=161 | | -9x-1=17 | | x^3-4x^2-36x+144=0 |